Dictionary of The Modern Politics of Southeast Asia - Liow, Joseph Chinyong, 1972- (Abingdon: Routledge, 2023)
The past three decades since the end of the Cold War have been a time of remarkable change for Southeast Asia. Long seen as an arena for superpower rivalry, Southeast Asia is increasingly coming into its own by locating itself at the forefront of regional integration initiatives that involve not only the states of the region, but major external powers such as the United States, China, India, Japan, and Australia. Extensively updated and revised in light of these changes and developments, this fifth edition of Dictionary of the Modern Politics of Southeast Asia remains indispensable. This new edition starts with profiles of each Southeast Asian country, before providing over 500 alphabetically arranged individual entries, each containing detailed accounts and analyses of major episodes and treaties, political parties and institutions, civil society movements, and regional and international organizations. Biographies of significant political leaders and personalities, both past and present, are also provided. Entries are comprehensively cross-referenced, and an index by country directs readers to all entries concerning a particular country. The Dictionary concludes with an extensive bibliography that serves as a guide to further reading. An essential one-stop reference book, this book is an indispensable tool for all scholars and students of Asian politics and international affairs, and a vital resource for journalists, diplomats, policy makers, and others with an interest in the region.
Previous edition: 2015.
Includes bibliographical references and index.
Joseph Chinyong Liow is Dean and Tan Kah Kee Chair Professor of Comparative and International Politics at the College of Humanities, Arts, and Social Sciences, Nanyang Technological University, Singapore, where he is also Professor at the S. Rajaratnam School of International Studies. He is the author of The Politics of Indonesia-Malaysia Relations (2005) and co-editor of The Routledge Handbook of Asian Security Studies (2010, with Sumit Ganguly and Andrew Schobell) and Order and Security in Southeast Asia: Essays in Memory of Michael Leifer (2005, with Ralf Emmers), all published by Routledge.
Keywords: Politics and government; Southeast Asia -- Politics and government -- 1945- -- Dictionaries; Southeast Asia; Dictionaries